Experimental model-based linearization of a S.I. engine gas injector flow chart - Pipitone, Emiliano (Strojniški vestnik, 2014)
Experimental tests previously executed by the authors on the simultaneous combustion of gasoline and gaseous fuel in a spark ignition engine revealed the presence of strong nonlinearities in the lower part of the gas injector flow chart. These nonlinearities arise via the injector outflow area variation caused by the needle impacts and bounces during the transient phenomena that take place in the opening and closing phases of the injector and may seriously compromise the air-fuel mixture quality control for the lower injection times, thus increasing both fuel consumption and pollutant emissions. Despite the extensive literature about the operation and modelling of fuel injectors, there are no known studies focused on the nonlinearities of the gas injector flow chart and on the way they can be reduced or eliminated. The authors thus developed a mathematical model for the prediction of mass injected by a spark ignition (S.I.) engine gas injector, validated through experimental data. The gas injector has been studied with particular reference to the complex needle motion during the opening and closing phases, which may strongly affect the amount of fuel injected. In this work, the mathematical model previously developed has been employed to study and determine an appropriate injection strategy in order to linearize the injector flow chart to the greatest degree possible. The injection strategy proposed by the authors is based on minimum injection energy considerations and may be easily implemented in current engine control units (ECU) without any hardware modification or additional costs. Once calibrated by means of simulation, this strategy has been validated by experimental data acquired on an appropriately equipped injector test bench. As a result, the real injector flow chart has been substantially improved, reducing its deviation from linearity to one third of the original flow chart, which is an excellent result, especially if the typical measurement dispersion of the injected mass is taken into account. The injection strategy proposed by the authors could extend the linear behaviour of gas injectors and improve the fuel supply by means of a simple software update of the ECU, thus obtaining higher engine efficiency and lower pollutant emissions.
Keywords: modeliranje vbrizgavanja goriva; motorji z notranjim zgorevanjem; optimalna strategija vbrizgavanja; plinasta goriva; vžigalne svečke